Effect of heat treatment on the microstructural evolution and mechanical properties of GH4099 fabricated by lase powder bed fusion - Yuanhong Qian; Liangxian Gu; Rong Chen; Haiou Yang; Zhiyong Li; Zhaowen Cui; Shuya Zhang (Journal of Materials Research and Technology)
In this study, the effect of solution and aging heat treatments on the microstructure and mechanical properties of GH4099 superalloy fabricated lase powder bed fusion (L-PBF) was investigated.The microstructure of as-manufactured L-PBF-built GH4099 alloy has elongation grain with an average grain size of 33.8 μm and fine cellular dendrites with an average spacing of 400 nm along the building direction. The grain structure of L-PBF-built GH4099 alloy is relatively complex and the grain boundary morphology is irregular. The morphology factor of the grains in the as-built GH4099 alloy primarily ranges between 0.3 and 0.4, with a notable inverse relationship between grain size and morphology factor. The L-PBF-built GH4099 alloy underwent complete recrystallization recrystallization when the solution temperature is 1120 °C and the holding time is extended to 4 h. With an increase in the solution temperature, the time required for complete recrystallization decreases progressively. As epitaxial columnar crystals are progressively replaced by recrystallized grains, the correlation between grain size and morphology factor gradually diminishes. The selection of solution and aging treatment parameters is based on the established relationships between the minimum solution time, temperature, and recrystallization behavior as well as the aging time, temperature, and hardness. The hardness of the fully recrystallized sample reached 460HV after solution at 1140 °C for 2 h and aging at 800 °C for 6 h, while the non-fully recrystallized sample reached 470HV after solution at 1120 °C for 1 h and aging at 750 °C for 8 h.The optimal heat treatment system of L-PBF-built GH4099 alloy is solid solution at 1140 °C for 2h, then aging at 800 for 6h. Under the optimal heat treatment regime, the longitudinal and transverse specimens have yield strengths of 714 and 753 MPa, tensile strengths of 1197 and 1230 MPa, and elongations of 45.3% and 38.9%, respectively.